OPTIMIZING THE LEGISLATIVE FUNCTION OF THE CIREBON REGENCY DPRD - Siska Karina; Zidan Abdul Aziz; Muhammad Riyan Faizz; Qothrunnada Syahira Ramadian; Rifa Lutfiani (Ann Publisher, 2025)
Abstract : Background. The Regional House of Representatives (DPRD) has three main functions: legislation, budget, and supervision. Legislation is vital in forming quality Regional Regulations (Perda) responsive to the community's needs. However, this function often experiences challenges in its implementation, such as a lack of public participation, limited resources, clashes with political interests, and weak coordination with the executive. Aims. This study analyzes obstacles to the DPRD's legislative function and examines optimization strategies through institutional approaches, capacity building of DPRD members, and strengthening community participation. Methods. This research method uses an empirical juridical method with interviews with the head of the legislative section (kabag) and the Chairman of the DPRD. Result. The study's results show that optimizing the DPRD's legislative function can be achieved by planning a more participatory regional legislation program (Prolegda), improving the quality of academic manuscripts, and continuously training legislative members. Conclusion. The DPRD's legislative function has a crucial role in the local government system, especially in forming regional regulations (Perda). However, its implementation still faces various obstacles, such as many Regional Regulations that are not resolved, are not implemented, or overlap with the regulations above, and weak coordination between the DPRD and the Regional Regulations. Implementation. Factors that hinder the implementation of the legislative function include synchronization with central regulations, the readiness of academic manuscripts and draft regional regulations, and limited discussion time.